196 GENE THERAPY USING RECOMBINANT ADENO-ASSOCIATED VIRUS/HER-2/NEU LOADING OF DENDRITIC CELLS FOR A POTENT CELLULAR MEDIATE IMMUNE RESPONSE AGAINST LYMPHOMA PRIMARY TUMORS. (1st January 2006) - White, E.; Chiriva-Internati, M.; Grizzi, F.; Cobos, E.
Abstract : Purpose: Recent studies demonstrate that recombinant adeno-associated virus (rAAV)-based antigen-loading of dendritic cells (DC) generates significant and rapid cytotoxic T lymphocyte (CTL) responses in vitro. As a more extensive analysis of the rAAV system, we used a self-antigen, Her-2, expressed in many cancers including breast and ovarian cancer, in particular, lymphoma. Methods: The AAV vectors were found to be able to transduce up to 85% of DC and the transduced DC displayed higher levels of CD80, CD83, CD86, and CD1a over controls. Autologous PBMC/LCL targets and Her-2/neu positive lymphoma primary cancer cell. Generation of CTL and test their function by Cr(51) release assay against LCL/Her-2/neu target and relative controls. Summary: We used the Her-2/neu gene, divided into 3 overlapping segments for insertion into AAV. The three Her-2 subgenes are aa 153-653, 403-906, and 76-1255. Using only one stimulation, significant MHC class I-restricted, anti-Her-2-specific CTL killing was demonstrated against a Her-2/neu-positive lymphoma primary cancer cell line. Using synthetic antigen-positive target cells with the three Her-2 subgenes and the primary lymphoma positive for Her-2/neu for a target, we stimulated highest CTL killing. The killing was done using specific Her-2(403-903)CTL against a target present in the particular peptide and inserted by rAAV AAV/Her-2(403-906)/Neo in the LCL. Conclusion: These data suggest that AAV-based antigen loading of DC is highly effective for generating a CTL response against lymphoma tumor.